Unveiling Similes in Olivia Rodrigo's GUTS: Crafting Emotional Narratives through Lyrics: English - siti14 jamila; Ahmad Yusuf Firdaus; Dwi Taurina Mila Wardhani (JOEY: Journal of English Ibrahimy, 2025)
This study examined the types and meanings of Numerous similes in Olivia Rodrigo's album Guts song lyrics. Similes, which create direct comparisons between two things using words like "like" or "as," were used to enhance emotional expression and bring vivid imagery to the lyrics. Using methods of qualitative, the examined every song to find instances of similes, classify them according to their type, and decipher the meanings using Dancygier and Sweetser's (2014) simile theory and Griffiths' (2006) meaning of Theory. The data was also interpreted using Spardley's methodology, which includes domain, taxonomic, componential, and cultural theme analysis. Twenty-two similes were found in the study, comprising ten examples with a broad scope and twelve with a limited scope. Additionally, it found three instances of utterance meaning and 19 instances of sender's meaning, indicating that sender's meaning and limited-scope similes was more prevalent in the album.